2009
DOI: 10.1590/s1020-49892009000600009
|View full text |Cite
|
Sign up to set email alerts
|

Estudio sobre la exposición ocupacional a sangre y fluidos corporales en el personal de enfermería de un hospital de referencia de Buenos Aires, Argentina

Abstract: These results signal a risk alert for OBBFE among health care workers and underscore the need for improving standards and surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
0
1
0
11
Order By: Relevance
“…Therefore, these measures should be aligned with the task in hand while considering potential exposure to blood and organic fluids 2 . Direct contact with patients, combined with the type and frequency of nursing procedures performed, increase occupational exposure risk of nursing staff to infectious material 4 . However, research studies demonstrated that the use of personal protective equipment (PPE) was still limited among health professionals, especially among nursing staff 5 - 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these measures should be aligned with the task in hand while considering potential exposure to blood and organic fluids 2 . Direct contact with patients, combined with the type and frequency of nursing procedures performed, increase occupational exposure risk of nursing staff to infectious material 4 . However, research studies demonstrated that the use of personal protective equipment (PPE) was still limited among health professionals, especially among nursing staff 5 - 8 .…”
Section: Introductionmentioning
confidence: 99%
“…A exposição ocupacional a material biológico provoca danos à integridade física, mental e social constituindo os acidentes, que podem ser auto ou heteroinfligidos -os agravos (1) . Este tipo de agravo tem sido um dos mais frequentes entre os trabalhadores de enfermagem (2)(3)(4)(5)(6)(7) .…”
Section: Introductionunclassified
“…Para melhor visualização e sistematização das categorias, causas primárias e secundárias dos acidentes ocorridos apresentamos o Quadro 1. dISCUSSÃO Neste estudo, houve uma elevada taxa de acidentes, quando comparada à de países desenvolvidos (6) e uma frequência elevada ao se comparar com países vizinhos (7) . Compreendemos que o fato de fazer o estudo na unidade contribuiu para o registro dos agravos.…”
Section: Introductionunclassified
See 2 more Smart Citations